Comparative Genomics and Transduction Potential of Enterococcus faecalis Temperate Bacteriophages - Yasmin, Azra (American Society for Microbiology (ASM), 2010)
To determine the relative importance of temperate bacteriophage in the horizontal gene transfer of fitness and virulence determinants of Enterococcus faecalis, a panel of 47 bacteremia isolates were treated with the inducing agents mitomycin C, norfloxacin, and UV radiation. Thirty-four phages were purified from culture supernatants and discriminated using pulsed-field gel electrophoresis (PFGE) and restriction mapping. From these analyses the genomes of eight representative phages were pyrosequenced, revealing four distinct groups of phages. Three groups of phages, ΦFL1 to 3, were found to be sequence related, with ΦFL1A to C and ΦFL2A and B sharing the greatest identity (87 to 88%), while ΦFL3A and B share 37 to 41% identity with ΦFL1 and 2. ΦFL4A shares 3 to 12% identity with the phages ΦFL1 to 3. The ΦFL3A and B phages possess a high DNA sequence identity with the morphogenesis and lysis modules of Lactococcus lactis subsp. cremoris prophages. Homologs of the Streptococcus mitis platelet binding phage tail proteins, PblA and PblB, are encoded on each sequenced E. faecalis phage. Few other phage genes encoding potential virulence functions were identified, and there was little evidence of carriage of lysogenic conversion genes distal to endolysin, as has been observed with genomes of many temperate phages from the opportunist pathogens Staphylococcus aureus and Streptococcus pyogenes. E. faecalis JH2-2 lysogens were generated using the eight phages, and these were examined for their relative fitness in Galleria mellonella. Several lysogens exhibited different effects upon survival of G. mellonella compared to their isogenic parent. The eight phages were tested for their ability to package host DNA, and three were shown to be very effective for generalized transduction of naive host cells of the laboratory strains OG1RF and JH2-2.